Motoneuron firing and isomyosin type of muscle fibres in prior polio. Issue 10 (October 1989) - Borg, K; Borg, J; Dhoot, G; Edström, L; Grimby, L; Thornell, L E
Abstract : In patients with prior polio there was an excessive use of remaining motor units and an absence of type II muscle fibres in the tibialis anterior (TA). In the present study, eight subjects with prior polio with more than 90% type I fibres in the TA were examined. The aim was to elucidate whether the lack of type II muscle fibres was due to a selective loss of motoneurons with high threshold and high axonal conduction velocity or due to a muscle fibre transition from type II to type I. There was no decrease of the proportion of motoneurons with high threshold and high axonal conduction velocity. Monoclonal antibodies against fast and slow myosin heavy chains (MHC) were used as histochemical markers and many muscle fibres of type I according to ATPase stainability showed a binding of both anti-fast and anti-slow MHC. It is suggested that the type I muscle fibre dominance in prior polio subjects with excessive use of TA during walking is due to a muscle fibre transition from type II to type I and not to a loss of one class of motor units.